2019
DOI: 10.1002/htj.21409
|View full text |Cite
|
Sign up to set email alerts
|

Development of cold‐hot water dispenser with thermoelectric module systems

Abstract: In the present study, the results of a cold-hot water dispenser with a thermoelectric module system (TMS) are presented. The cold-hot water dispenser with thermoelectric module system consists of a cold water loop, a hot water loop, a coolant loop, and a thermoelectric module. The thermoelectric cooling and heating modules consist of four and two water blocks, nine and three thermoelectric plates, respectively. The cooling and heating capacities obtained from the cold-hot water dispenser with TMS are compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Next, Almodfer et al [44] used the random vector to determine the efficiency of a solar-powered thermoelectric cooler. The most productive studies have been continuously done [45][46][47][48][49][50][51][52][53]. They apply the thermoelectric cooling module for many systems, including; cold-hot water dispensers [45,46], sensible air cool-warm fan [47], liquid cooler module [48], cooling CPU [49], electric generator [50], the cooling module with nanofluid as coolant [51], and cooling electrical vehicle battery module [52,53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, Almodfer et al [44] used the random vector to determine the efficiency of a solar-powered thermoelectric cooler. The most productive studies have been continuously done [45][46][47][48][49][50][51][52][53]. They apply the thermoelectric cooling module for many systems, including; cold-hot water dispensers [45,46], sensible air cool-warm fan [47], liquid cooler module [48], cooling CPU [49], electric generator [50], the cooling module with nanofluid as coolant [51], and cooling electrical vehicle battery module [52,53].…”
Section: Introductionmentioning
confidence: 99%
“…The most productive studies have been continuously done [45][46][47][48][49][50][51][52][53]. They apply the thermoelectric cooling module for many systems, including; cold-hot water dispensers [45,46], sensible air cool-warm fan [47], liquid cooler module [48], cooling CPU [49], electric generator [50], the cooling module with nanofluid as coolant [51], and cooling electrical vehicle battery module [52,53]. The thermoelectric cooling modules use water and nanofluids as working fluids flowing through the systems.…”
Section: Introductionmentioning
confidence: 99%
“…A novel compact heat sink module is proposed by Wiriyasart et al [18], the module uses water as the loop fluid, and thermoelectric devices are added to it, thereby improving the temperature difference between the cold and hot sides and the output power. In addition, they also did some research on thermoelectric coolers [19][20][21]. The one-dimensional energy equilibrium approach is used by Liu et al [22] to study the performance of variable cross-section TEGs, their results showed that compared with the traditional thermoelectric leg, the variable cross section thermoelectric leg can always improve the maximum conversion efficiency of TEGs.…”
Section: Introductionmentioning
confidence: 99%